A one health perspective on antimicrobial susceptibility testing and multidrug resistance patterns of Escherichia coli from exotic pets in Banda Aceh, Indonesia - Teuku Reza Ferasyi; Mahdi Abrar Abrar; Ismail Ismail; Masda Admi; Wahyu Eka Sari; Awaluddin Awaluddin; Rosalia Rosalia; Lailia Dwi Kusuma Wardhani; Baidillah Zulkifli; Teuku Shaddiq Rosa; Intan Noor Aina Kamaruzaman; Adela Hemelikova (Universitas Airlangga, 2026)
Antimicrobial-resistant Escherichia coli is widely used as an indicator organism in antimicrobial resistance (AMR) surveillance, with most studies focusing on livestock. However, AMR in companion animals, particularly exotic pet species in Indonesia, remains poorly explored. This preliminary study aimed to presumptively detect resistant E. coli in pigeons, civets, and iguanas housed in pet shops located on Seutui’s main road in the city of Banda Aceh, Indonesia. A descriptive cross-sectional study was conducted to collect 15 fecal samples from pigeons (n = 9), civets (n = 3), and iguanas (n = 3) kept in three pet shops from June to July 2025. E. coli isolates were confirmed using Eosin Methylene Blue agar (EMBA). Antibiotic susceptibility testing (AST) was performed using the Kirby–Bauer method against five antibiotics: cephalothin (CEP, 30 μg), sulfamethoxazole/trimethoprim (SXT, 25 μg), ciprofloxacin (CIP, 5 μg), tetracycline (TE, 30 μg), and chloramphenicol (CHL, 30 μg). Presumptive E. coli positivity was confirmed in 46.67% (7/15) of the fecal samples. Species-specific positivity rates were 44.44% (4/9), 33.33% (1/3), and 66.67% (2/3) in pigeons, civets, and iguanas, respectively. The multidrug resistance (MDR) profile across all isolates was 85.71% (6/7). Species-specific MDR was observed in 75.00% (3/4) of pigeon-derived isolates and 100% of both civet-derived (n = 1) and iguana-derived isolates (n = 2). In conclusion, multidrug-resistant E. coli was detected in pigeons, civets, and iguanas housed in pet shops. A One Health approach and mitigation framework should be implemented to control AMR in pet shops and other relevant veterinary settings.